2021
DOI: 10.3390/jimaging7100211
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Molecular Imaging for Atherosclerotic Plaque

Abstract: Atherosclerosis is a well-known disease leading to cardiovascular events, including myocardial infarction and ischemic stroke. These conditions lead to a high mortality rate, which explains the interest in their prevention, early detection, and treatment. Molecular imaging is able to shed light on the basic pathophysiological processes, such as inflammation, that cause the progression and instability of plaque. The most common radiotracers used in clinical practice can detect increased energy metabolism (FDG),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…Many research reported different imaging modalities for identification and visualization of AS lesions or plaque vulnerability, 19,43 such as micro-CT imaging, 44 intravascular ultrasound (IVUS) imaging, 45 optical coherence tomography (OCT) imaging, 46 contrast-enhanced MRI, 47 as well as CEUS. [48][49][50] However, these researches mainly focused on monitoring the outcomes of plaque formation, such as assessment of plaque neovascularization, macrophage distribution, vascular plaque burden and atherosclerotic plaque composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research reported different imaging modalities for identification and visualization of AS lesions or plaque vulnerability, 19,43 such as micro-CT imaging, 44 intravascular ultrasound (IVUS) imaging, 45 optical coherence tomography (OCT) imaging, 46 contrast-enhanced MRI, 47 as well as CEUS. [48][49][50] However, these researches mainly focused on monitoring the outcomes of plaque formation, such as assessment of plaque neovascularization, macrophage distribution, vascular plaque burden and atherosclerotic plaque composition.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, molecular imaging can show specific biological pathways or cellular processes for a better understanding of the molecular events responsible for plaque destabilization. 19,20 Ultrasound molecular imaging technology presented great potentials to characterize and image the occurrence and development of diseases on the molecular level. [21][22][23] In particular, the development of a wide range of imaging contrast agents, functionalized with targeting ligands such as antibodies, peptides or aptamers, 24,25 could be promising for probing the molecular biomarkers of the atherosclerotic processes, promoting the translational potential of novel technologies.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is most pronounced in hypoxic areas where it compensates for inefficient glucose utilization [ 48 ]. The possibilities and limitations of this technique were discussed in a previous study [ 7 ].…”
Section: Evolution Of An Atherosclerotic Plaquementioning
confidence: 99%
“…Choline incorporation into the cell membrane is a multi-stage process, the main stages of which include entering the cell via specific transport mechanisms, phosphorylation by choline kinase, and conversion to phosphatidylcholine [ 49 ]. This technique was discussed in a previous study [ 7 ].…”
Section: Evolution Of An Atherosclerotic Plaquementioning
confidence: 99%
See 1 more Smart Citation